An Attempt to Identify Factors Influencing Retirement Decisions in Poland - Ruzik-Sierdzińska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Discussions on how to prevent negative economic consequences of ageing of societies have resulted in the reforms that should prolong labour market participation and postpone retirement of longer living generations. Pension systems are among those reformed most frequently. Also in Poland – since the beginning of economic transformation in the early 1990s – retirement rules have changed many times. Pre‑retirement benefits and allowances have been introduced to help those who became unemployed at an older age. Since 2009 early retirement is not possible any more (with some exceptions), the standard retirement age continued to increase since 2013 and then it decreased again in 2017. The aim of the paper is to analyse the driving forces of retirement in Poland. Such knowledge is important to develop proper policies and expectations about labour supply decisions. We have analysed what factors influenced retirement decisions in the last decade, with a special focus on pension system regulations. The main data sources used in this paper are Labour Force Survey (BAEL) data for the years 2005–2016 and the Social Insurance Institution statistics. Probabilities of retirement from the labour force were presented and discussed. Then, individual BAEL data for persons aged 50–74 in the years 2013–2016 were used to estimate logistic regression models of odds of labour market inactivity. The results show that education or health status are significant factors influencing retirement decisions in Poland. Additionally, older workers react to economic incentives for retirement created by the pension system, mainly the retirement age.